Recruitment mechanisms and therapeutic implications of tumor-associated macrophages in the glioma microenvironment - Zhou, Xianzhe; Jin, Guishan; Zhang, Junwen; Liu, Fusheng (Frontiers in Immunology, 2023)
As one of the main components of the glioma immune microenvironment, glioma-associated macrophages (GAMs) have increasingly drawn research interest. Primarily comprised of resident microglias and peripherally derived mononuclear macrophages, GAMs are influential in a variety of activities such as tumor cell resistance to chemotherapy and radiotherapy as well as facilitation of glioma pathogenesis. In addition to in-depth research of GAM polarization, study of mechanisms relevant in tumor microenvironment recruitment has gradually increased. Suppression of GAMs at their source is likely to produce superior therapeutic outcomes. Here, we summarize the origin and recruitment mechanism of GAMs, as well as the therapeutic implications of GAM inhibition, to facilitate future glioma-related research and formulation of more effective treatment strategies.